Virus and virus-like diseases of grapevine in Hungary - Lázár, J.; Bisztray, Gy. D. (International Journal of Horticultural Science, 2011)
Viruses and viroids are submicroscopic infectious particles which can cause disease symptoms on grapevine. These parasites are depending completely on the energy metabolism of the plant cell. To enter the host cell plant viruses depend on injuries or on transmission via invertebrates (insects, nematodes, etc.). Viruses are classified by many characters including particle morphology, host range and information content of the genome. At present about 70 viruses including 7 viroids infecting grapevine are known. In single or mixed infections they are potentially detrimental to the quality and quantity of grape production in any growing area of the world. Some viruses can cause severe economic damage in vineyards. In Hungary many important viruses and viroids have been detected in grape. This review summarises characteristics of viruses and the results of detection and characterization of virus and virus like diseases of grapevine in Hungary. The identification of the causal agent, its transmission, geographical distribution and the development of the diagnostic methods are also discussed.